2018
DOI: 10.1038/s41467-018-03880-y
|View full text |Cite|
|
Sign up to set email alerts
|

Chemically triggered drug release from an antibody-drug conjugate leads to potent antitumour activity in mice

Abstract: Current antibody-drug conjugates (ADCs) target internalising receptors on cancer cells leading to intracellular drug release. Typically, only a subset of patients with solid tumours has sufficient expression of such a receptor, while there are suitable non-internalising receptors and stroma targets. Here, we demonstrate potent therapy in murine tumour models using a non-internalising ADC that releases its drugs upon a click reaction with a chemical activator, which is administered in a second step. This was en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
265
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(266 citation statements)
references
References 35 publications
1
265
0
Order By: Relevance
“…Electron density on the tetrazine affects the tautomerization of the intermediates with a decreased electron density inhibiting release. Nevertheless, tetrazines with two alkyl substituents react with carbamate‐modified trans ‐cyclooctenes at a rate of up to 54.7 m −1 s −1 in PBS at 37 °C, which is the fastest reported dissociative iEDDA reaction that also provides high release yields …”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron density on the tetrazine affects the tautomerization of the intermediates with a decreased electron density inhibiting release. Nevertheless, tetrazines with two alkyl substituents react with carbamate‐modified trans ‐cyclooctenes at a rate of up to 54.7 m −1 s −1 in PBS at 37 °C, which is the fastest reported dissociative iEDDA reaction that also provides high release yields …”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%
“…Dissociative bioorthogonal reactions can also be combined with antibody–drug conjugates (Scheme B). Researchers have developed antibody–drug conjugates in which drugs were linked to the antibody through a trans ‐cyclooctene linker . Rossin et al.…”
Section: Applications Of Dissociative Bioorthogonal Reactions In the mentioning
confidence: 99%
“…Treatment of tumor‐bearing mice with 4 cycles of the 65 – 66 combination led to remarkable anticancer effects and this activity was significantly higher than the one showed by single‐treatment with an analogous MMAE‐based ADC equipped with the Val‐Cit linker . Following a different approach, Chen, Gao and co‐workers applied the “click and release” protocol with the TCO‐tetrazine pair to the tumor‐targeted enzyme instructed supramolecular self‐assembly (EISA) context .…”
Section: When and Where: Linker Cleavage Promoted By External Stimulimentioning
confidence: 99%
“…He successfully showed that tetrazine triggers the release of the cell‐permeable peptide monomethyl auristatin E in mice bearing cancer xenografts. This work demonstrated that TCO‐based prodrug systems offer a new approach for controlled drug release by targeting non‐internalising receptors; although the activation was relatively slow, this could well be beneficial for controlled and longer‐term dosing . Recently, the authors showed that this TCO‐based release mechanism could also be used for masking esters and alcohols, while Pluth reported a thiocarbamate linkage that allowed the release of carbonyl sulfide as a gastrotransmitter .…”
Section: Tetrazines As Activators For Prodrugsmentioning
confidence: 99%